Microscopic Microwave Oven [news brief]. (IEEE spectrum)
Modeled on West Point, the National Military Academy of Afghanistan is often referred to as "East Point." The government hopes graduates will help rebuild roads, bridges, and an electricity grid ravaged by decades of war and neglect.